AMPA/kainate receptor activation within the prelimbic cortex is necessary for incubated cocaine-craving - Huerta Sanchez, Laura L.; Tadros, Mirette G.; Doan, Hoa H. T.; Vo, Sylvie V.; Chaudhari, Sanil R.; Li, Taylor L.; James, Peter B.; Na, Audrey Y.; Cano, Fernando J.; Kippin, Tod E.; Szumlinski, Karen K. (Frontiers in Psychiatry, 2025)
IntroductionThe incubation of craving is a behavioral phenomenon in which cue-elicited craving increases during a period of drug abstinence. Incubated cocaine-craving is associated with increased extracellular glutamate within the medial prefrontal cortex (mPFC) and this release, particularly within the prelimbic (PL) subregion, is necessary for incubated cocaine-craving. A potential candidate mediating these incubation-driving effects of glutamate release within the PL are alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors.MethodsTo investigate the role of mPFC AMPA receptors (AMPARs) in incubated craving, male and female Sprague-Dawley rats were trained to self-administer cocaine for 6 h/day for 10 consecutive days. Either during early or later withdrawal, rats were infused intra-PL with the AMPA/kainate receptor antagonist NBQX (0 or 1 µg/0.5 µl per side), followed by 30-min tests for cue-induced responding. Immunoblotting was also conducted to relate the expression of incubated cocaine- and sucrose-craving to AMPAR subunit expression within mPFC subregions.ResultsIntra-PL NBQX blocked incubated craving expressed in late, but not early, withdrawal. In contrast, an intra-PL NBQX infusion increased cue-induced cocaine-seeking in female rats tested in early withdrawal. No incubation-related changes in AMPAR subunit expression were detected within the PL or IL of rats of either sex and no estrus-associated changes in subunit expression were detected in female rats exhibiting incubated cocaine-craving. In contrast, elevated GluA1 expression was observed within the IL of male rats exhibiting an incubation of sucrose-craving.DiscussionTogether, these findings indicate a necessary role for AMPAR/kainate receptors within the PL in driving incubated cocaine-craving and suggest that AMPAR/kainate receptors located within the IL may be involved also in sucrose-craving selectively in males.